Independent predictors of clinical outcomes after surgical correction of degenerative lumbar scoliosis: a retrospective cohort study - Xiao Xiong; Feng Wang; Ruiling Wang; Tong Tong (Frontiers in Surgery, 2026)
Objective To identify the independent risk factors and predictive parameters for clinical outcomes in patients undergoing surgical intervention for degenerative lumbar scoliosis (DLS). Methods A retrospective analysis was conducted on 134 patients with DLS who underwent posterior decompression and fusion. Clinical prognosis was evaluated using the Oswestry Disability Index (ODI). Patients were categorized into “better prognosis” and “poor prognosis” groups based on postoperative functional recovery. Potential risk factors—including patient demographics, surgical data, and radiographic/imaging parameters—were analyzed using multivariate analysis. Receiver operating characteristic (ROC) curves were utilized to determine optimal threshold values for predicting surgical efficacy. Results One hundred and thirty-four patients with degenerative lumbar scoliosis who underwent posterior surgery were included in this study. The analysis showed that the subcutaneous fat tissue thickness (SFTT) , MRI-based vertebral bone quality (VBQ), Quantitative Computed Tomography (QCT) , degree of kyphosis correction, sagittal balance correction distance were independent predictors of poor prognosis. ROC curve analysis showed that correction degree of kyphosis >20.23°, sagittal balance correction distance >2.92 cm, QCT >104.6 mg/cm 3 , VBQ <2.88, SFTT <13.5 mm were indicating good clinical efficacy. Conclusions Posterior decompression and fixed fusion significantly alleviate pain and enhance quality of life in patients with DLS. Adequate correction of kyphosis and sagittal balance is paramount for achieving optimal functional outcomes. Furthermore, our findings that SFTT, VBQ, and QCT are significantly associated with prognosis suggest that aggressive anti-osteoporosis treatment and early paraspinal muscle exercises may be beneficial for improving long-term surgical success. Future interventional studies are warranted to confirm this potential causal relationship.